STANDARD STATES FOR THE ACTIVITIES OF MINERAL SURFACE SITES AND SPECIES - Sverjensky D.A. (My University, 2003)
A standard state commonly used for the activities of surface sites and surface species is the hypothetical 1.0 Molar standard state, which is implied by the use of molarity-based equilibrium constants. An undesirable practical consequence is that the magnitudes of such equilibrium constants are directly dependent on properties of the solid sorbent such as the site density and surface area. For reactions forming binuclear complexes, the magnitudes of the equilibrium constants even depend on the amount of solid. Although widely used, such equilibrium constants cannot be directly compared with each other without correction for differences in the properties or the amount of the solid. In the present study, new more general and useful standard states are proposed, leading to equilibrium constants independent of the surface area, site density, and the amount of the solid sorbent. Analytical relationships between the old and the new standard states enable conversion of equilibrium constants from one standard state to the other. These results have implications for several different types of surface complexation studies, including studies that correlate and compare equilibrium adsorption constants for different solids, sensitivity-analysis studies of the fitting of surface charge data as functions of pH and ionic strength, and studies employing correlations involving aqueous equilibrium constants for the purpose of predicting equilibrium constants for surface reactions.